Toxicidad aguda del extracto alcohólico e hidroalcohólico de hojas y corteza de Matisia cordata Bonpl. en nauplios de Artemia franciscana - Rios Arce de Maldonado, Yolanda (2024)
In the field of phytochemical and pharmacological research, the evaluation of the acute toxicity of plant extracts is a crucial step in determining their safety and potential therapeutic applications. This study focuses on Matisia cordata Bonpl., a plant with known medicinal properties, whose leaves and bark have been selected for analysis. Objective: to determine the acute toxicity of the alcoholic and hydroalcoholic extract of leaves and bark of Matisia cordata Bonpl. in nauplii of Artemia franciscana. Methodology: A. franciscana eggs were stored at a temperature of 2 – 8 °C until use, artificial seawater was prepared using commercially available Instant Ocean salt, where the eggs were incubated in 3% Instant Ocean solution for 48 to 72 hours. Newly hatched nauplii were used for acute toxicity exposure of M. cordata leaf and bark extracts, which were collected for convenience and tested at 10, 100 and 1000 ppm. Results: The LC50 of the two extracts studied is greater than 1000 ppm. Conclusion: None of the extracts are considered toxic